Delivery of monocyte lineage cells in a biomimetic scaffold enhances tissue repair - Michael S. Hu; Graham G. Walmsley; Leandra A. Barnes; Kipp Weiskopf; Robert C. Rennert; Dominik Duscher; Michael Januszyk; Zeshaan N. Maan; Wan Xing Hong; Alexander T.M. Cheung; Tripp Leavitt; Clement D. Marshall; et al. (JCI Insight, 2017)
The monocyte lineage is essential to normal wound healing. Macrophage inhibition or knockout in mice results in impaired wound healing through reduced neovascularization, granulation tissue formation, and reepithelialization. Numerous studies have either depleted macrophages or reduced their activity in the context of wound healing. Here, we demonstrate that by increasing the number of macrophages or monocytes in the wound site above physiologic levels via pullulan-collagen composite dermal hydrogel scaffold delivery, the rate of wound healing can be significantly accelerated in both wild-type and diabetic mice, with no adverse effect on the quality of repair. Macrophages transplanted onto wounds differentiate into M1 and M2 phenotypes of different proportions at various time points, ultimately increasing angiogenesis. Given that monocytes can be readily isolated from peripheral blood without in vitro manipulation, these findings hold promise for translational medicine aimed at accelerating wound healing across a broad spectrum of diseases.